The Income Analysis Of Vegetables Farming With Hydroponic System In Samarinda City, Indonesia - Zaini, Achmad; Maqshuddi, Idham; ., Juraemi (Advances in Social Sciences Research Journal, 2018)
The Vegetable farming with hydroponics system is a good prospect. the system is appropriately practiced in urban areas with narrow land. The aim of study to know the income level of vegetables farming with hydroponics system in Samarinda city, Indonesia. The number of respondents taken as many as 13 people with census method. Data were collected by field observation and direct interview with respondent. The result of study show that total costs of vegetables consisting of mustard greens, lettuce and celery was Rp